AlCl3-catalyzed insertion of isocyanides into nitrogen–sulfur bonds of sulfenamides. Issue 12 (18th March 2015) - Shiro, Daisuke; Fujiwara, Shin-ichi; Tsuda, Susumu; Iwasaki, Takanori; Kuniyasu, Hitoshi; Kambe, Nobuaki
Graphical abstract: Abstract: Lewis acid-catalyzed insertion of isocyanides2 into nitrogen–sulfur bonds of sulfenamides1 was developed. This method provided a convenient method for the synthesis of isothioureas3 . Among Lewis acids examined, AlCl3 brought about the best result. Acetic acid assisted one-pot preparation of unsymmetrical ureas was also described.